The girl who soared over Fairyland and cut the moon in two - Valente, Catherynne M. 1979- (Feiwel and Friends, 2013)
Longing for a new adventure that will reunite her with Ell, the Wyverary, and Saturday, September is spirited away to the moon and charged with saving Fairyland from a moon-Yeti who wields mysterious powers